Keutamaan Dalam Pemilihan Faktor Ketersediaan E-Pembelajaran Di UTHM - Muhamad Hisham, Muhamad Safwan; Ramlan, Rohaizan (Research in Management of Technology and Business, 2020)
The rapid development of information and communication technology from various aspects causes the education system to be affected by changes such as e-Learning method. Effective e-Learning implementation strategies are a combination of four-party collaboration namely university, support staff, lecturers and students. Universiti Tun Hussein Onn Malaysia (UTHM) uses blended learning as a e-learning tool. The main purpose of the study is to identify the factor of readiness for implementing e-Learning among UTHM students. Among the factors studied are organizational readiness, human resource development, human resource readiness, specific infrastructure readiness, common infrastructure readiness, and legal and formal readiness. This study conducted back in 2018 using purposive sampling method. The questionnaires given to 270 students from Faculty of Technology Management and Business (FPTP) and Faculty of Computer Science and Information Technology (FSKTM). The population was selected based on active faculty’s that are using the e-learning system in UTHM. The data obtained were analyzed using the Analytic Hierarchy Process (AHP) expert choice model to ranking up the factors in e-learning implementation. The results show that the ranking number one is the readiness of organizational factor in implementing e-Learning. Followed by specific infrastructure readiness, human resource development, human resource readiness, common infrastructure readiness and legal and formal readiness. The findings measured UTHM’s readiness to implement e-learning in full-scale operations in future through improving factors that are in low ranking.